2018
DOI: 10.3184/003685018x15166183479666
|View full text |Cite
|
Sign up to set email alerts
|

From Fundamental Science to Product: A Bottom-up Approach to Sunscreen Development

Abstract: Despite the pivotal role of ultraviolet (UV) radiation in sustaining life on Earth, overexposure to this type of radiation can have catastrophic effects, such as skin cancer. Sunscreens, the most common form of artificial protection against such harmful effects, absorb UV radiation before it reaches vulnerable skin cells. Absorption of UV radiation prompts ultrafast molecular events in sunscreen molecules which, ideally, would allow for fast and safe dissipation of the excess energy. However, our knowledge of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 73 publications
(133 reference statements)
0
45
0
Order By: Relevance
“…A further study by Horbury et al [ 107 ] has investigated SM more closely to explore the influence of solvent viscosity on the proposed photodynamics [ 107 ]. A comprehensive review of this study has been reported in a previous publication [ 108 ]. Briefly, following TEAS measurements, the study revealed that the time constant assigned to the relaxation of the excited-state population along the trans–cis photoisomerisation coordinate ( viz.…”
Section: Case Studiesmentioning
confidence: 99%
“…A further study by Horbury et al [ 107 ] has investigated SM more closely to explore the influence of solvent viscosity on the proposed photodynamics [ 107 ]. A comprehensive review of this study has been reported in a previous publication [ 108 ]. Briefly, following TEAS measurements, the study revealed that the time constant assigned to the relaxation of the excited-state population along the trans–cis photoisomerisation coordinate ( viz.…”
Section: Case Studiesmentioning
confidence: 99%
“…8,[26][27][28] Sunscreen filters work by facilitating the safe dissipation of absorbed, potentially harmful, UVR as heat to the surrounding environment. 29 This review will highlight the main experimental, and to a lesser extent, complementary theoretical techniques used to track molecule-photon interactions (photochemistry), and hence unravel the photoprotection mechanisms underpinning MAAs. This, in turn yields important insight into why nature has chosen these particular sunscreen filters as photoprotective species.…”
Section: Mycosporine and Mycosporine-like Amino Acidsmentioning
confidence: 99%
“…31,33 A typical photoacoustic signal is displayed in Figure 3(c), this signal is formed from two contributions: (1) the thermal expansion of the solute upon the heat being delivered through radiationless relaxation and (2) the volume change induced in the solute and solvent. 28,29 Through performing the experiment at multiple temperatures and comparing with a known calorimetric standard, the initial peak to peak amplitude can be assigned as the energy lost from the solute, H in Figure 3(c). 28,29 A calorimetric standard is usually a compound that presents a similar absorption and undergoes no radiative transitions, that is, fluorescence or phosphorescence.…”
Section: Tracking the Energy Flow Within Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…From a photophysical perspective, this translates to short-lived excited states, with excited state population returning to the electronic ground state (S 0 ) within a picosecond (10 -12 second) lifetime or less, typically via internal conversion (IC). [10][11][12] Fast excited state relaxation ensures not only that the UV filter is less vulnerable to harmful photochemistry but also that it is quickly 'recycled' and thus able to re-absorb UV radiation. In turn, this 'recycling' of the UV filter ensures the commercial sunscreen formulation maintains its photoprotective performance for longer periods of time.…”
Section: Introductionmentioning
confidence: 99%